Ventricular Septal Rupture Complicating Delayed Acute Myocardial Infarction Presentation During the COVID-19 Pandemic - Alsidawi, Said (JACC Case Rep, 2020)
The rate of mechanical complications of acute myocardial infarction has declined. Recent publications raised concerns over the reduction in cardiac catheterization laboratory activation for ST-segment myocardial infarction (STEMI) during the coronavirus disease-2019 (COVID-19) pandemic. We present 2 recent cases of ventricular septal rupture in patients who presented to our institution with delayed STEMI. (Level of Difficulty: Intermediate.)